Answer:
[tex]8(x^2+y^2)-4x-30y+23=0[/tex]
Step-by-step explanation:
Distance formula
[tex]\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}[/tex]
Let P(x, y) = any point on the locus
Let A = (0, 2)
Let B = (-2, 3)
If a point moves such that its distance from (0, 2) is one third distance from (-2, 3):
[tex]PA=\dfrac{1}{3}PB[/tex]
Therefore, using the distance formula:
[tex]\implies \sqrt{(x-0)^2+(y-2)^2}=\dfrac{1}{3}\sqrt{(x-(-2))^2+(y-3)^2}[/tex]
Square both sides:
[tex]\implies x^2+(y-2)^2=\dfrac{1}{9}[(x+2)^2+(y-3)^2][/tex]
[tex]\implies x^2+y^2-4y+4=\dfrac{1}{9}(x^2+4x+4+y^2-6y+9)[/tex]
Multiply both sides by 9:
[tex]\implies 9x^2+9y^2-36y+36=x^2+4x+4+y^2-6y+9[/tex]
[tex]\implies 8x^2+8y^2-4x-30y+23=0[/tex]
[tex]\implies 8(x^2+y^2)-4x-30y+23=0[/tex]